Effects of Presleep Cognitive Intrusions on Subjective Sleep and Next-Day Cognitive Performance in Insomnia. Issue 5 (September 2020) - Ballesio, Andrea; Ghezzi, Valerio; Vacca, Mariacarolina; Ottaviani, Cristina; Lombardo, Caterina
Abstract: Presleep cognitive intrusions about next-day activities, or proprioceptive and environmental stimuli, are thought to trigger insomnia in neurocognitive models. Recent research showed that intrusive cognitions at bedtime may interact with sleep in influencing next-day emotional functioning; their effects on cognitive functioning, however, is largely unknown. We tested the effects of presleep cognitive intrusions on subjective sleep and next-day cognitive performance in 80 participants, either with chronic insomnia or good sleepers. Presleep intrusions were inspected using a validated questionnaire and sleep was assessed with a sleep diary. Cognitive functioning the following morning was measured using a task-switching paradigm assessing executive functions. Structural equation modeling with manifest variables (i.e., path analysis) shows that presleep cognitive intrusions predicted increased sleep onset latency and wake after sleep onset, and lowered sleep efficiency. Moreover, task-switching accuracy was independently predicted by presleep cognitive intrusions in the previous night in those with insomnia but not in controls, beyond the effects of trait anxiety, task-switching components, and previous night's sleep. Findings confirm detrimental effects of presleep intrusions on sleep continuity and suggest the presence of links between presleep conscious activity and next-day executive performance in patients with insomnia, with the need to better elucidate potential mediators.